Uniformity investigation of deposited nanoparticles via pulse direct current (DC) in electrophoretic deposition (EPD) / Rabiatul Adawiyah Abdol Aziz, Noor Fitrah Abu Bakar and Mohd Nazli Naim - Abdol Aziz, Rabiatul Adawiyah; Abu Bakar, Noor Fitrah; Naim, Mohd Nazli (Research Management Institute (RMI), 2013)
Nowadays, with increasing thrust on nanostructured materials, Electrophoretic Deposition (EPD) technique is being viewed with more interest for assembly of nanoparticles. It covers a wide range of applications such as photonic materials, high density magnetic data storage devices, microchip reactors and biosensors. Obviously, the use of water/aqueous implies advantages such as a faster kinetics, in addition to important health, environmental, and cost benefits. However, it causes a number of problems in electrophoretic forming mainly related to electrochemical reaction in the electrodes when current is passed through, which seriously affects the efficiency of the process and the uniformity of the deposit. Different sizes of standard nanoparticles i.e. polystyrene latex (PSL) particles will be diluted with milipore water into several concentration media and it will be sonicated . pH of the aqueous will be prepared in acid and alkaline media by adding HCl and NaOH respectively. Carbon and copper electrode will be submerged in the media. EPD with Direct Current (DC) voltage will be applied during the deposition process. The deposited particle will be weighed with balancer. For the case of pulse DC, different frequency of pulse cycle will be applied. The deposited particles will be analyzed using X-ray Diffraction (XRD). The morphology of the deposited naoparticles will be analyzed by using Scanning Electron Microscopy (SEM). Distribution of the deposited particle will be characterized iether by using EDS analyzer in SEM. In this work, we propose to evaluate the uniformity of the deposited particles with EPD technique, pulse DC will be applied in the experiment with different frequency of pulse cycle.